Analysis of the Implementation of Fiqh Principles and Ta'zir Sanctions for Violations of Contracts - Muhammad Najiyullah Firmansyah; Imroatul Azizah (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
This abstract aims to analyze the integration of Islamic economic principles with law enforcement through a review of the Compilation of Islamic Economic Law (KHES) and Islamic Criminal Law. The main study lies in how Islamic jurisprudence (fiqh) principles function as a philosophical and operational basis in mitigating economic disputes. Using normative legal research methods, this article examines various contracts in KHES that often intersect with aspects of legal violations. The research findings show that Islamic jurisprudence principles such as "al-ashlu fi al-'uqud alibahah" (the original law of the contract is permissible) and "al-dhararu yuzal" (harm must be eliminated) provide flexibility as well as ethical boundaries in modern transactions. However, when a breach of contract occurs that contains elements of fraud (tadlis) or embezzlement, Islamic economic law does not only stop at civil settlement, but also intersects with the realm of Islamic criminal law through the ta'zir sanction mechanism. This analysis confirms that the enforcement of the Islamic Law (KHES) requires synergy with the principles of criminal law to create a deterrent effect against economic behavior that harms the public.